Fitting food to circumstances potential contributions of Philippine culinary heritage to disaster risk reduction - Sta. Maria, Felice (Budhi: a Journal of Ideas and Culture, 2020)
Cultural legacies include a society's emergency preparedness. Geological hazards such as the movement of the West Valley fault will result in a metadisaster. Food security is fundamental to community resilience, a strategy for disaster risk reduction. Heritage food practices may contribute to food security during emergencies and disasters. Seasonal weather conditions and natural calamities have forced continuing developments in Philippine cuisine. Conveniemce foods, home and urban gardening, as well as food preservation continue to be altered appropriately to variations in societal anxieties, aspirations, and hopefully now, disaster preparedness.